2013
DOI: 10.1111/jch.12073
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Severe Obstructive Sleep Apnea Syndrome in Hypertensive Outpatients

Abstract: We attempted to validate a two-stage strategy to screen for severe obstructive sleep apnea syndrome (s-OSAS) among hypertensive outpatients, with polysomnography (PSG) as the gold standard. Using a prospective design, we recruited outpatients with hypertension from medical outpatient clinics. Interventions included: 1) assessment of clinical data; 2) home sleep testing (HST); and 3) 12-channnel, in-laboratory PSG. We developed models using clinical or HST data alone (single-stage models) or clinical data in ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 40 publications
(98 reference statements)
0
43
0
3
Order By: Relevance
“…18 In-laboratory polysomnography is unsuitable for screening because of complexity, expense and inaccessibility. 19 In our study, the severity of OSAHS was assessed using diagnostic polysomnography in a sleep laboratory. A Pearson's correlation analysis was then conducted to assess the correlations between the TNF-α/IL-10 ratio and baseline and polysomnography variables.…”
mentioning
confidence: 99%
“…18 In-laboratory polysomnography is unsuitable for screening because of complexity, expense and inaccessibility. 19 In our study, the severity of OSAHS was assessed using diagnostic polysomnography in a sleep laboratory. A Pearson's correlation analysis was then conducted to assess the correlations between the TNF-α/IL-10 ratio and baseline and polysomnography variables.…”
mentioning
confidence: 99%
“…Full-night attended PSG is an expensive diagnostic procedure and its availability is limited in many countries. However, studies have shown that portable monitors for home sleep testing in addition to clinical data (e.g., BMI) can be used to identify patients with OSAS without incurring greater costs (Gurubhagavatula et al 2013). Eijsvogel et al showed that a two-step screening with a questionnaire and a nasal flow recording was a promising way to screen for OSAS in a healthy working population (Eijsvogel et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few studies have proposed predictors or screening models that were restricted to hypertensive individuals . Only one of these studies was performed in a primary care setting .…”
Section: Discussionmentioning
confidence: 99%